View of the ceiling of the mandapa in the Someshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
View of the ceiling of the mandapa (pillared hall) in the Someshwar Mahadev Temple. The ceiling consists of concentric circular rings made of cusps or fractals. The innermost ring features brackets adorned with sculptures. All concentric rings of the ceiling are profusely carved with sculptures, floral motifs, and geometric patterns.